FORMULASI STRATEGI PENGEMBANGAN BISNIS MENGGUNAKAN PENDEKATAN BUSINESS MODEL CANVAS (BMC) DAN SWOT ANALYSIS DALAM UPAYA MENINGKATKAN DAYA SAING PADA PIRING SENG COFFEE & CO TUNJUNGAN SURABAYA - Achmad Hambali; Sonja Andarini (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
The culinary business has good prospects, including in the coffee shop business. Piring Seng Coffee & Co is one of the many coffee shops in Surabaya so that it is faced with a situation of dynamic competition and challenges. Therefore, Piring Seng Coffee & Co needed to formulate the right business model and needed a new strategy in order to increase its competitiveness and market share. This research aims to analyze the business model for Piring Seng Coffee & Co using the Business Model Canvas approach, which is then evaluated based on the SWOT analysis so that recommendations for improvements to the block elements of the business model are generated. Qualitative descriptive is the method used in this study with data analysis techniques, namely Business Model Canvas (BMC) and SWOT analysis including using IFAS and EFAS. Data collection techniques through interviews, participatory observation, and documentation study. Respondents in this study consisted of the owner, operational manager, employees, and consumers of Piring Seng Coffee & Co which were selected purposively as many as 11 people. The results showed the SWOT analysis diagram of the strategic direction leading to "Growth Oriented Strategy", namely supporting aggressive strategies, which then became an input for improving the Business Model Canvas. From its implementation, it shows that improvements are recommended on the nine elements of the Business Model Canvas with the resulting strategy being input for management. Keywords: Piring Seng Coffee & Co, Business Model Canvas, SWOT, coffee shop.